2017
DOI: 10.1097/sla.0000000000001648
|View full text |Cite
|
Sign up to set email alerts
|

Acid Sphingomyelinase Inhibition in Stored Erythrocytes Reduces Transfusion-Associated Lung Inflammation

Abstract: Acid sphingomyelinase inhibition in stored pRBCs offers a novel mechanism for improving the quality of stored blood.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
38
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 32 publications
(39 citation statements)
references
References 51 publications
1
38
0
Order By: Relevance
“…14 In addition, previous work from our laboratory indicates that the microparticle concentration present in stored human pRBC units equals or exceeds the number of microparticles found in stored murine units. 30 Additionally, previous studies have shown that higher MP concentrations increase their biological effects in a dose-response fashion. 14 Thus, we suspect that potential harm from microparticles from stored pRBC units may become clinically relevant in patients who receive multiple units of pRBCs, especially in the setting of massive transfusion.…”
Section: Discussionmentioning
confidence: 99%
“…14 In addition, previous work from our laboratory indicates that the microparticle concentration present in stored human pRBC units equals or exceeds the number of microparticles found in stored murine units. 30 Additionally, previous studies have shown that higher MP concentrations increase their biological effects in a dose-response fashion. 14 Thus, we suspect that potential harm from microparticles from stored pRBC units may become clinically relevant in patients who receive multiple units of pRBCs, especially in the setting of massive transfusion.…”
Section: Discussionmentioning
confidence: 99%
“…For example, in C. elegans , inhibition of a lipid flippase that transfers phosphatidylethanolamine from the outer leaflet of the plasma membrane to the inner leaflet promotes vesicle budding [42,43]. Alterations in ceramide content on the outer leaflet via activation of acid sphingomyelinase can also induce membrane curvature and trigger microvesicle release [44–46]. Shedding of vesicles has been shown to occur from multiple aspects of the plasma membrane, including at microvillar protrusions of intestinal epithelial cells [47] and from cells engineered to overexpress hyaluronan synthase [48], as well as from cilia [49].…”
Section: Ev Biogenesis and Releasementioning
confidence: 99%
“…Recent research has demonstrated that acid sphingomyelinase (Asm) activity in RBCs is associated with MP formation and treatment of RBCs with amitriptyline, an Asm inhibitor, inhibited MP formation during RBC storage. This treatment was associated with reduced lung inflammation following blood transfusion in a murine model (41). Together, these data demonstrate the significant contribution of RBC-derived MPs to immunomodulation after transfusion.…”
Section: Introductionmentioning
confidence: 99%